Valores relativos ao trabalho e carreira: um estudo com jovens trabalhadores - Lisboa, Jonas Coutinho (2022)
This study aims to analyze the predictability of Work Values on Career Adaptability and Career Barriers, from the perspective of young workers in the labor market. To reach the objective, a quantitative, descriptive survey was conducted. The study was conducted in a sample of 320 young people, aged 18 to 24 years, 61.9% (N = 198) being female. Considering the proposed model, chose to use structural equation modeling (SEM), and other statistical analyzes in relation to gender were also explored. The main result indicated evidence that the Work Values construct explains 39% (R²) of the Career Adaptability construct variance. This result supports the importance of internal demands, represented by the values that young workers attribute to work, about career adaptability, a assumption with little empirical evidence so far. Predictability between Work Values and Career Barriers was not identified. However, significant differences were found between gender and perception of Career Barriers. Finally, the results are discussed, emphasizing the idea that, according to what young people consider important in their work environment, they tend to better develop the qualities to adapt to career changes. Suggestions for future research are pointed out.